IMPROVING STUDENTS’ READING COMPREHENSION THROUGH LISTEN-READ-DISCUSS (L-R-D) STRATEGY AT SMA NEGERI 1 TONDANO - Makasidamo, Griselda Eusebia; Muntuuntu, Meity; Rorimpandey, Rinny S. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This researcher focused on improving the students’ reading comprehension through Listen-Read-Discuss (L-R-D) strategy. The research sample consisted of 26 students at class XI IPA 3. A quantitative research method was used, employing a Pre-Experimental Design form of one group pre-test and post-test design. To collect data, the instrument used in this research was a multiple-choice test consisting of 25 items. Data were analyzed using mean score formula to see significant differences between the pre-test and post-test scores. The results showed that there was a significant difference between pretest and posttest scores. The result of students’ pre-test was 66,76 and the post-test was 71,15. The different score between pre-test and post-test was 30,13. The result of this research is indicated that mean score of post-test was higher 4,39% more than pre-test. This shows that the use of the LRD method is effective in improving students’ reading comprehension at SMA Negeri 1 Tondano. In addition, student said that LRD strategy really helped them to be active in the learning process so that they could understand the reading well. In conclusion, this research recommends that the LRD method be used as an alternative learning in teaching reading especially reading comprehension in schools.